(untitled) (Revista Innova Educación, 2021)
The evaluation from its multiple models starts from being an essential component in any teaching process. This article aimed to carry out a review on the state of the art of formative assessment with a view from its various strategies in regular basic education in students of regular basic education. A documentary review was carried out in the Scopus, Web of Science, Scielo and Redalyc databases, using selection and exclusion criteria. It was found that formative assessment strategies should be used to enrich the development of teaching-learning. It was concluded that formative evaluation strategies are the starting point to strengthen student learning, in this way it was found that cooperative work encourages unity in the classroom; at the same time, the students share information about the activity they are doing, creating an atmosphere of peace and tranquility in the classroom. The student is the center of the formative and shared evaluation process, showing that self-evaluation and peer evaluation strengthens the development of their abilities and skills.